The Influence of Product Innovation and Utilization of Digital Marketplace Platforms on the Sustainability of East Javanese Culinary Businesses - Wina Nurhayati; Didik Setiawan (STIEKOP MALANG PRESS, 2026)
Purpose – This study investigates the determinants of business sustainability for East Javanese culinary Micro, Small, and Medium Enterprises (MSMEs), focusing on the roles of product innovation and digital marketplace adoption. Design/methodology/approach – A quantitative research design was employed, utilizing a structured questionnaire distributed to 250 owner-managers of East Javanese culinary MSMEs. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to test the proposed hypotheses. Findings – The results indicate that both product innovation (? = 0.385, p < 0.001) and digital marketplace utilization (? = 0.421, p < 0.001) have significant positive effects on business sustainability. Furthermore, competitive advantage was found to partially mediate the relationship between these independent variables and sustainability. The model explains 58.7% of the variance in business sustainability. Research limitations/implications – Limitations include a cross-sectional design, self-reported data, and a focus on a specific regional context (East Java) which may limit generalizability. The study provides practical insights for entrepreneurs and policymakers aiming to enhance the resilience and long-term viability of regional culinary heritage businesses in the digital era. Originality/value – These findings underscore the critical importance of continuous innovation and digital transformation for culinary MSMEs to thrive in a competitive market. It fills a research gap by providing an integrated empirical model that simultaneously tests the influence of product innovation and digital marketplace utilization on the sustainability of culturally specific culinary businesses.